Migrants and refugees : equitable education for displaced populations - Brown, Elinor L.; Krasteva, Anna (International advances in education., 2013)
International Advances in Education: Global Initiatives for Equity and Social Justice is an international research monograph series of scholarly works that primarily focus on empowering students (children, adolescents, and young adults) from diverse current circumstances and historic beliefs and traditions to become non-exploited/non-exploitive contributing members of the global community. The series draws on the research and innovative practices of investigators, academics, and community organizers around the globe that have contributed to the evidence base for developing sound educational policies, practices, and programs that optimize all students' potential. Each volume includes multidisciplinary theory, research, and practices that provide an enriched understanding of the drivers of human potential via education to assist others in exploring, adapting, and replicating innovative strategies that enable ALL students to realize their full potential. This volume provides the reader with promising policies and practices that promote social justice and educational opportunity for the many displaced populations (migrants, asylum-seekers, refugees, and immigrants) around the globe. The volume is divided into four sections that offer: (1) insights into the educational integration of displaced children in industrialized nations, (2) methods of creating pedagogies of harmony within school environments, (3) ways to nurture school success by acknowledging and respecting the cultural traditions of newcomers, and finally (4) strategies to forge pathways to educational equity. Overall, this volume contributes to the body of knowledge on equitable educational opportunities for displaced youth and will be a valuable resource for all who seek to enable the displaced a place at the political, economic, and social table of civil society.